THE REPRESENTATION OF THE AMERICAN ARMY'S TREATMENT OF OKINAWANS DURING WORLDWAR II: A SEMIOTIC ANALISIS OF "THE ISLAND SONG" AND "A MILLION TEARS" BY KAJUFUMI MIYAZAWA - Ari Yuda Laksmana, - (2008)
ABSTRACT This research, entitled The Representation of The American Army's Treatment of Okinawans During World War II (A Semiotic Analysis of "The Island's Song" and "A Million Tears" by Kazufumi Miyazawa), was directed to discover how the American Army's treatment to Okinawan represented in The Island's Song and A Million Tears written by Kazufumi Miyazawa. A qualitative approach was conducted to answer the following questions: (1) what issues are raised in The Island's Song and A Million Tears, (2) how is the American Army's treatment of Okinawan represented semioticaly in The Island's Song and A Million Tears, and (3) why is it represented as such. The samples of the research were two lyrics written by Kazufumi Miyazawa. The research found that the lyrics represent the Okinawan misery afflicted by the traumatic war, during and afterward in which they were described as sadness separation and living in lost. Through sign identification, intertextuality, and biographical review, the research also discovered that the song author intends to deliver (a) the beauty of Okinawa island which was represented with the blooming Deigo flower; (b) the horrible and traumatic attack of American army which was represented with the signs such the wind, storm and waves; (c) the sad story of separation between soldier and nurse within the war represented with the Uji and Okra field events, and; (d) the intention of the song author to spread the truth in political manner about what happened in Okinawa to all people over the world which was represented in the repetition stanzas.